Channeling assessments in English language learning via interactive online platforms - Astri Yulia; Nor Azilah Husin; Faiz I Anuar (Studies in English Language and Education, 2019)
Technology adoption in classrooms has impacted the way educational practitioners conduct assessments. Online quizzes are preferred compared to paper-pencil based tests. However, very few information that explains the contribution of online assessment towards holistic attainment of students in English. The present study aimed at examining the effects of online assessments on students’ performance. This research employed a quasi-experimental study to evaluate the role of interactive online assessments toward students’ performance in English. Eighty-six undergraduate students in TESL participated in this study; 53 were randomly assigned to the online group while 33 were assigned to the control group. The research computed t-tests to compare the performance of both groups on five different assessments. The results revealed that the online assessment group performed better on four assessments tested—listening and reading skills. The control group performed significantly higher on the assessment that involved presentation (evaluated speaking skill). These findings indicate that online assessments enhance students’ mastery of listening, reading, and writing skill but rather not so much influence on verbal skills. This research implies that educational practitioners should not entirely rely on interactive online platforms. To incorporate the blended-learning approach, classroom activities must consist of a combination of online and offline strategies.